A new solution to mitigate hydropeaking? Batteries versus re-regulation reservoirs. (10th February 2019) - Anindito, Yoga; Haas, Jannik; Olivares, Marcelo; Nowak, Wolfgang; Kern, Jordan
Abstract: Hydropower plants frequently operate at high output during peak hours and at low output (or even shutoff) during off-peak hours. This scheme, called "hydropeaking", is harmful to downstream ecosystems. Operational constraints (minimum flows, maximum ramps) are frequently used to mitigate the impacts of hydropeaking. However, they reduce the operational flexibility of hydroelectric dams and increase the operational cost of power systems. Another approach to mitigating ecological impacts from hydropeaking is using structural measures, such as re-regulation reservoirs or afterbays. The first contribution of our work is to study the cost-effectiveness of these re-regulation reservoirs in mitigating ecological impacts from subdaily hydropeaking. Our second contribution is assessing energy storage (specifically, batteries) to mitigate the financial impacts of implementing peaking restrictions on dams, which represents the first attempt in the literature. Understanding these mitigation options is relevant for new hydropower dams, as well as for existing ones undergoing relicensing processes. For this, we formulate an hourly mixed-integer linear optimization model to simulate the annual operation of a power system. We then compare the business-as-usual (unconstrained) hydropower operations with ecologically constrained operations. The constrained operation, by limiting hydropower ramping rates, showed to obtain flows close to the natural streamflow regime. As next step, we show how re-regulation reservoirs and batteries can help to achieve these ecological constraints at lower costs. While the former are cost-effective for a very broad range of investment costs, the latter will be cost-effective for hydropeaking mitigation from 2025 onwards, when their capital costs have fallen. If more stringent environmental constraints are imposed, both solutions become significantly more attractive. The same holds for scenarios of more renewable generation (in which the operational flexibility from both alternatives becomes more valuable). After 2030, batteries can match the cost-effectiveness of expensive re-regulation reservoirs. Our findings are valuable for policy and decision makers in energy and ecosystem conservation. Highlights: We compare re-regulation reservoirs with batteries for hydropeaking mitigation. We develop profitability curves that track profitability alongside capital costs. Re-regulation reservoirs are highly cost-effective (easily recoup capital costs). Batteries will become economically viable for hydropeaking mitigation by 2025. Results will inform public/private sector management of dams' environmental impacts.